Mobile-based monitoring system for an automatic cat feeder using Raspberry Pi - Nenny Anggraini; Dzul Fadli Rahman; Luh Kesuma Wardhani; Nashrul Hakiem (Universitas Ahmad Dahlan, 2020)
In a Saheeh hadith it is explained that the cat is a clean animal that is free from najis, so keeping a cat is not something that is forbidden. One of the things that is important when keeping a cat is feeding. However, keeping a cat at home takes time and effort. In this digital era, the use of technology has penetrated all aspects of life. The objective of this research is to create a monitoring system for an automatic cat feeder using a webcam and a stepper motor that is connected to a Raspberry Pi as the main controller. The webcam can take pictures (photographs or videos) processed with the fswebcam and the avconv functions on the Raspberry Pi. The stepper motor can rotate the feed valve by utilising a General-Purpose Input Output (GPIO) pin and a program which is inserted into the Raspberry Pi. Next, the Raspberry Pi will be connected to the Internet and a server network so that the system control can be done remotely by using a web browser or web view on a mobile. The overall function of the system in the form of feeding the cat either directly or scheduled, as well as monitoring of photographs or videos around the feed. The results of a questionnaire showed that this system has a need value of 87.3% of 79 respondent cat keepers, meaning cat keepers will be greatly helped by the existence of this system.